2012
DOI: 10.5271/sjweh.3279
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive function among sons of women who worked in dentistry

Abstract: Objective Exposure to elemental mercury vapor can impair neurological function as it is neurotoxic in doses higher than usually found in dentistry. Little is known about the potential effects of fetal exposure to elemental mercury among offspring of female dental workers. We investigated cognitive function among offspring of women working in dentistry at the time of their pregnancy.Methods We compared results for cognitive function examinations taken by the majority of young men in Sweden at the time of compul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In another earlier study, we found no association between maternal employment in dentistry and adverse effects on cognitive function among male offspring [23] . It is probable that the military tests for cognition utilized in the previous study were undertaken only by those deemed fit enough to be considered for military service, potentially excluding subjects suffering from neurological disease such as epilepsy or intellectual disability.…”
Section: Introductionmentioning
confidence: 86%
“…In another earlier study, we found no association between maternal employment in dentistry and adverse effects on cognitive function among male offspring [23] . It is probable that the military tests for cognition utilized in the previous study were undertaken only by those deemed fit enough to be considered for military service, potentially excluding subjects suffering from neurological disease such as epilepsy or intellectual disability.…”
Section: Introductionmentioning
confidence: 86%
“…Therefore, exposure to Hg in a poorly ventilated room could cause significant health risks to not only healthcare workers but also to patients and their families. Previous studies have reported that occupational exposure to Hg in dentists and dental assistants leads to irritation, headaches, neurobehavioral consequences (memory loss, depression, behavioural abnormalities, sleep, and personality alterations), and arthralgias [10][11][12]. Also, a study in nursing professionals has suggested certain associations between Hg exposure and Parkinson, Alzheimer, arthritis, negative effects on the thymus gland, and the psychomotor development of nurses' children [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…12 Occupational exposure leads to irritability, headache, neurobehavioral effects (memory loss, depression, behavioral changes, and sleep and personality alterations), and muscle disorders such as arthralgia in dentists or dental assistants. [13][14][15][16] In nursing professionals, certain associations have been suggested between mercury exposure and Alzheimer disease, Parkinson disease, arthritis, negative effects on the thymus gland, and the psychomotor development of nurses' children. [17][18][19][20] In view of these health risks, the European Union has restricted the use of various mercury-containing products.…”
Section: Introductionmentioning
confidence: 99%